2020
DOI: 10.1097/nan.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Making the Most of Midlines

Abstract: Decision-making for vascular access device selection is becoming increasingly complex as new technologies come to market and efforts to reduce central line-associated bloodstream infections increase. This retrospective review of 165 midline catheter outcomes was undertaken after a cluster of unexpected failures occurred in a large academic medical center in the southeastern United States. Mean dwell time for midline catheters was 8.5 days; 62.8% lasted to therapy completion, and complications occurred in 15.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…Another factor supporting the view that the MCL is a safe catheter is the lack of cases of phlebitis observed in the present study, a complication that has been reported elsewhere (Caparas & Hung, 2017; Dumont et al, 2014; Meyer, 2020; Penoyer et al,2021; Sharp et al, 2014; Spiegel et al, 2020; Xu et al, 2016). Factors that may have contributed to the lack of phlebitis and infiltration include the use of an ultrasound‐guided MST, the insertion in deep veins of the arm (with a larger diameter and flow allowing a greater haemodilution) (Adams et al, 2016; Alexandrou et al, 2011; Caparas & Hung, 2017), the catheter material and length, the selection of the basilic and brachial veins rather than the cephalic vein, the site of insertion (ZIM TM green zone) (Dawson, 2011) and the use of a sutureless securement device.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Another factor supporting the view that the MCL is a safe catheter is the lack of cases of phlebitis observed in the present study, a complication that has been reported elsewhere (Caparas & Hung, 2017; Dumont et al, 2014; Meyer, 2020; Penoyer et al,2021; Sharp et al, 2014; Spiegel et al, 2020; Xu et al, 2016). Factors that may have contributed to the lack of phlebitis and infiltration include the use of an ultrasound‐guided MST, the insertion in deep veins of the arm (with a larger diameter and flow allowing a greater haemodilution) (Adams et al, 2016; Alexandrou et al, 2011; Caparas & Hung, 2017), the catheter material and length, the selection of the basilic and brachial veins rather than the cephalic vein, the site of insertion (ZIM TM green zone) (Dawson, 2011) and the use of a sutureless securement device.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of thrombosis was lower than that found in other studies (Bahl et al, 2019;Campagna et al,2018; Klungboonkrong et al, 2015;Lisova et al, 2018;Meyer, 2020;Ruggles, & Ventura, 2016;Sharp et al, 2014;Warrington et al, 2012;Xu et al, 2016). Although previous research seems to indicate that placing the catheter tip beyond the axilla may not be safe due to a high risk of thrombosis (Gorski & Czaplewski, 2004;Moureau et al, 2015), the results of our study provide evidence for the safety of the subclavian location.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Recently, it was reported that in a small sample of 17 midline catheters, 90% experienced loss of blood return in a mean of 3 days. 23 Blood return was reestablished in 5 of the catheters using a troubleshooting algorithm that could be considered in other organizations.…”
Section: Complicationsmentioning
confidence: 99%